Percutaneous Minimally Invasive Fetoscopic Surgery: Ramah Ibu dan Janin - Marshalita, Nadya (Malang Journal of Midwifery (MAJORY); Vol 1 No 2 (2019): MAJORY, 2019)
Spina bifida is a neural tube defect in which incomplete closing of the spine membrane that occurs in the lumbar and sacral. The defect of spina bifida can be motoric defect or sensoric defect. Clinical manifestation of spina bifida can be appear as limb anaesthesia, total paralysis, incontinensia urine and alvi that can cause recurrent uronary tract infection, renal insufficiency, and nephropathy reflux. Spina bifida can cause hindbrain herniation and hydrocephalus. Diagnosis of spina bifida can use 2D ultrasonography, 3D ultrasonography, and MRI. Procedure surgery of spina bifida can be done with postnatal surgery, prenatal surgery, or percutaneous minimally invasive fetoscopic surgery. Percutaneous minimally invasive fetoscopic surgery is a procedure to close the defect of fetus while intrauterine using minimal access with three or four trocar and using partial amniotic carbon dioxide insufflation (PACI) without laparotomy or hysterectomy. The adventage of percutaneous minimally invasive fetoscopic surgery compare with postnatal surgery and prenatal surgery is improve baby’s motoric function, decrease risk of ventriculoperitoneal (VP) shunt, decrease hindbrain herniation, decrease fluid in hydrocephalus, decrease risk of preterm birth, decrease risk of spontaneous membrane rupture, oligohydramnione, uterine dehiscence, uterine rupture, less pain in two days, and mother can go home from the hospital in a weeks. Keywords: Spina bifida, percutaneous minimally invasive fetoscopic surgery, partial amniotic carbon dioxide insufflation (PACI)